2003
DOI: 10.1063/1.1628221
|View full text |Cite
|
Sign up to set email alerts
|

The heterogeneity of the hydroxyl groups in chabazite

Abstract: Two different clusters that have the topology of chabazite but different shapes have been used as a model for the Brønsted sites in chabazite. One of the clusters consists of eight tetrahedral atoms ͑8T͒ arranged in a ring and the other represents an intersection of two 8T rings. The adsorption of water and methanol on the two stable proton positions in chabazite has been studied using the B3LYP functional. The coordination of water and methanol with respect to the zeolite fragments were found to be similar, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…26 More accurate prediction of vibrational frequencies have been reported by inclusion of anharmonic contributions. 33,55 However, harmonic calculations still provide reasonable estimates for Brønsted acid properties at the surface. 17,25 The Bader charge method was used to quantify the electronic charge associated with specific atomic species.…”
Section: ■ Introductionmentioning
confidence: 99%
“…26 More accurate prediction of vibrational frequencies have been reported by inclusion of anharmonic contributions. 33,55 However, harmonic calculations still provide reasonable estimates for Brønsted acid properties at the surface. 17,25 The Bader charge method was used to quantify the electronic charge associated with specific atomic species.…”
Section: ■ Introductionmentioning
confidence: 99%
“…1. The nature of the four structurally-different acid sites in CHA-type zeolites has been studied by quantum chemical calculations; 3,[14][15][16]27,[30][31][32][33][34] the number of atoms in the unit cell of CHA is very small (36 atoms), which enables a rapid and easy calculation. However, experimental measurements of the solid acidity of CHA-type zeolites have not been carried out sufficiently; therefore no comparison between experimental and theoretical values has been performed.…”
Section: Introductionmentioning
confidence: 99%
“…We have studied adsorption of water on both proton sites, 35 and we have found that a more stable complex is formed with the proton position O 3 than O 1 . In this paper all calculations for the bare zeolite clusters and complex with water have been done for the proton attached to O 3 .…”
Section: A Zeolite Cluster Without Watermentioning
confidence: 99%